Kasvatuksen tulevaisuus : professori Oiva K. Kyöstiön juhlakirja - Antikainen, Ari.; Husén, Torsten; Holmes, Brian; Becker, Helmut; De Sanctis, Philippo M.; Andersson, Håkan; Syrjälä, Leena; Downing, John.; Saarinen, Pirkko; Kari, Jouko; Koskenniemi, Matti; Nurmi, Veli.; et al. (Helsingissä [Hki] : Otava, 1983)
Summaries.
Tekstiä myös ruotsiksi ja englanniksi.
Keywords: Kyöstiö, O. K., -- 1913-1987.